(untitled) (INNOVATIVE ECONOMY, 2026)
Kryvtsov A.O. ASSESSMENT OF SOCIAL RETURN ON INVESTMENT AS AN INNOVATIVE TOOL FOR MANAGING SOCIAL ENTERPRISES Purpose. The aim of this article is to provide a theoretical substantiation for assessing social return on investment as an innovative management tool for social enterprises and to determine its functional potential within a strategic management system. Methodology of research. The theoretical and methodological basis of this article is based on the fundamental principles of modern economic theory, strategic management concepts, stakeholder theory, and the shared value creation paradigm. A combination of general scientific and specialized methods was used to achieve these goals: a systems approach to substantiate the role of social entrepreneurship as a new type of entity; generalization and analysis methods to clarify the conceptual framework and reveal the content of mixed value; a process approach to develop an algorithm for assessing the social return on investment and determining the stages of its implementation; and a comparative analysis to identify the advantages and limitations of using SROI compared to traditional financial indicators. Findings. The article provides a comprehensive theoretical and methodological substantiation for assessing social return on investment (SROI) as an innovative tool for managing social enterprises in the context of economic transformation and the growing importance of sustainable development. It highlights the problem of the inadequacy of traditional financial indicators for assessing the effectiveness of organizations focused on creating social value and proves the need to integrate social and economic results into a single strategic analysis system. The theoretical foundations of SROI, based on stakeholder theory, the resource approach, and the concept of mixed value, are revealed. It is substantiated that the application of the methodology allows establishing causal links between the resources invested and the social results achieved, quantifying and monetizing them, and calculating the social return ratio. It is shown that SROI performs analytical, strategic, and communication functions in the management system of social enterprises, contributes to increasing the transparency of activities, and forming an evidence base for social impact. The institutional features of the methodology’s implementation in Ukraine are analysed, in particular the influence of the regulatory environment, the level of development of management practices, and the problems of standardizing social indicators. The advantages and limitations of applying SROI from the perspective of practical management of social enterprises are identified. The focus is on substantiating the role of SROI as a modern management analytics tool in the activities of social enterprises. The importance of systematic measurement of social impact for improving the effectiveness of strategic planning, rational allocation of resources, and strengthening stakeholder trust is emphasized. Originality. For the first time, a conceptual model for integrating social return on investment (SROI) assessment into the strategic management system of social enterprises as an innovative tool for management analytics that ensures a balance between economic feasibility and verified social impact in the context of institutional transformations has been substantiated. Practical value. Practical recommendations for implementing the SROI methodology into the management practices of social enterprises have been improved. The proposed closed-loop management algorithm can be used by organizational leaders for strategic planning and increasing the investment attractiveness of impact investing projects. Furthermore, the identified institutional barriers and systematized advantages and limitations of the method will serve as a basis for developing industry standards for social impact in Ukraine. Key words: social entrepreneurship, social return on investment, SROI, social impact, strategic management, impact investing, monetization of social effects, mixed value.